Derivation and 97% Purification of Human Thyroid Cells From Dermal Fibroblasts - Ma, Risheng; Shi, Rui; Morshed, Syed A.; Latif, Rauf; Davies, Terry F. (Frontiers in Endocrinology, 2020)
Background: The success in rescuing thyroid deficiency in mice using thyroid cells derived from embryonic stem (ES) cells, together with the discovery of human induced pluripotent stem cells (iPSCs) from somatic cells, has raised the possibility of patient-specific thyroid cell replacement. In this study we demonstrate that human thyroid follicular cells can be derived from human iPSCs and show the ability of highly purified and differentiated cells to secrete thyroid hormone. Research Design and Methods: Human iPSCs were derived from adult skin fibroblasts using RNA reprogramming and differentiated in vitro into thyroid follicular cells by exposure to activin A, ethacridine and TSH as we have previously described for human ES cells. The resulting thyroid cells were then highly purified using double antibody cell sorting. Results: The iPSCs derived from human dermal fibroblasts showed stem cell-like morphologic changes and expressed pluripotent stem cell markers as assessed using qPCR, immunofluorescence staining and FACS analysis. These cells retained their pluripotential characteristics as shown by teratoma formation after murine transplantation. Definitive endoderm cells were induced with activin A and the transcription factor TAZ was significantly induced on ethacridine treatment and translocated to the nucleus. Thyroid transcription factors NKX2-1 and PAX8 were also highly expressed in activin A derived endoderm cells and further induced by ethacridine. Following terminal differentiation with TSH, there was enhanced thyroid follicle formation, high expression of the thyroid specific genes - TG, TPO, TSHR and NIS, and secretion of thyroid hormone (T4) in vitro. Furthermore, we were able to achieve a 97% purification of TSHR+/NIS+ expressing cells after differentiation using a single purification procedure. Conclusions: These findings demonstrate that mature adult dermal fibroblasts can be matured into human iPSCs which have the potential to form functional thyroid follicular cells. This lays the groundwork for future person–specific thyroid regenerative therapy.